A supervisory control-based navigation architecture for autonomous robots in industry 4.0 environments - Gonzalez, Antonio Galiza Cerdeira (2019)
In this dissertation, a general architecture for mobile robot navigation in Industry 4.0 environments in which the open-loop behavior of the robot and the specifications are based on automata is presented. A modular supervisory control structure, which is the conjunction of two supervisors is proposed: the first one, that enforces the robot to follow the path defined by a planner, and the second one that guarantees the satisfaction of the specifications such as prevention of collisions, task and movement management. The proposed navigation architecture allows decentralized implementation, in which the modular supervisor is embedded in the mobile robot, whereas the planner can run in external agent. Such a feature makes the adaptation of the proposed navigation architecture to different environments easy. The navigation architecture proposed in this dissertation is illustrated by means of a simulation in a hypothetical environment that resembles a smart factory. An adaptation for multiple robots is also presented, also validated by simulations.